2019
DOI: 10.3390/ijms20092095
|View full text |Cite
|
Sign up to set email alerts
|

YY1/BCCIP Coordinately Regulates P53-Responsive Element (p53RE)-Mediated Transactivation of p21Waf1/Cip1

Abstract: Transactivation of p21 (cyclin-dependent kinase inhibitor 1A, CDKN1A) is closely related to the recruitment of transcription cofactors at the p53 responsive elements (p53REs) in its promoter region. Human chromatin remodeling enzyme INO80 can be recruited to the p53REs of p21 promoter and negatively regulates p21. As one of the key subunits of the INO80 complex, YY1 has also been confirmed to bind to the p53RE sites of p21 promoter. Importantly, YY1 was recently reported to be bound and stabilized by BCCIP (BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Therefore, we speculated whether YY1 also plays a role in p63-regulated enhancer–promoter interactions. It has already been shown that YY1 binds to the p53 protein [ 52 ], and p63 is a conserved homologue of p53; therefore, we investigated whether p63 can also interact with YY1. We conducted co-immunoprecipitation (Co-IP) experiments on the RBE_vector vs. RBE_over groups, and found that p63 and YY1 can bind to each other (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we speculated whether YY1 also plays a role in p63-regulated enhancer–promoter interactions. It has already been shown that YY1 binds to the p53 protein [ 52 ], and p63 is a conserved homologue of p53; therefore, we investigated whether p63 can also interact with YY1. We conducted co-immunoprecipitation (Co-IP) experiments on the RBE_vector vs. RBE_over groups, and found that p63 and YY1 can bind to each other (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by several authors (Ding, 2018;Sui, 2019;Meliala, 2020; showed that the transactivation of p21 (cyclin-dependent kinase inhibitor 1A) is closely related to the recruitment of transcription cofactors at the p53 responsive elements (p53REs) in its promoter region. Human chromatin remodeling enzyme INO80 can be recruited to the p53REs of the p21 promoter and negatively regulates p21 (Ding, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since it was reported that the transcription factor YY1 is an negative regulator of p53 as well as of p21 [60][61][62][63][64], another important protein for cell cycle regulation and that the loss of YY1 resulted in polyploidy and chromatid aberrations [65], we wanted to know whether we could rescue the Tcf21-induced MBM by the co-expression of YY1. Indeed, we observed a complete rescue of the MBM suggesting a role of YY1 in the differentiation of podocytes.…”
Section: Discussionmentioning
confidence: 99%